The Development of Canva Assisted Scientific Approach Teaching Materials to Improve Students’ Critical Thinking Ability on Junior High School - Ainy, Levina Aulya Quratul; Yuliani, Anik; Bernard, Martin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
Based on research at the school that schools still use conventional learning, so students are less involved or less interactive, therefore this study aims to find out whether the development of teaching materials in the form of worksheets on flat-sided geometrical material using a scientific approach assisted by the Canva application is feasible and makes students be interactive while knowing the feasibility of the teaching materials being developed, knowing the effectiveness of the teaching materials being developed and knowing the constraints faced by researchers during the development of teaching materials. The development research model used is the 4D development model. The research location chosen was Darul Falah Middle School with random selection of subjects. The research instruments used were validation sheets, student response sheets and five critical thinking skills test instruments. The results of the development of the teaching materials themselves, namely during the limited trials the validation results reached 80% with a proper interpretation and the practical results of the teaching materials were 84% with very practical interpretations, in the extensive trials the validation results reached 93% with very feasible interpretations and the results of the practicality of the materials teaching 86% with very practical interpretation. The results of this study indicate that the process of developing teaching materials is carried out well.